COMPARISON OF PSYCHOTROPIC NARCOTICS LAWS BASED ON INDONESIAN AND DUTCH LAW THE COMPARISON OF PSYCHOTROPIC NARCOTICS LAWS UNDER INDONESIAN AND DUTCH LAW - Riska Ruth Verarussy; Febby Mutiara Nelson (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The purpose of this study is to compare drug abuse is closely related to the distribution of illegal goods which is one of the criminal offenses throughout the world, especially in Indonesian and Dutch law. as the Criminal Code (KUHP) as a Dutch colonial legacy. During the Dutch colonial government, the Wetboek van Strafrecht voor Nederlands-Indie (Staatsblad 1915: 732) was enforced. Drugs and psychotropic substances can cause death if abused. The Netherlands allows the use of narcotics while Indonesia considers the use of narcotics to be illegal. The method used in this research is the method of legal comparison of the legal system of Indonesia and the Netherlands against the law of Narcotics and Psychotropic Drugs applied. The results of this study indicate that Indonesia and the Netherlands both apply the civil law system. The purpose is to find out the differences and similarities of criminal law of narcotics and psychotropic drugs Indonesia with the Netherlands. Indonesia designed legislation to prohibit the use and distribution of narcotics, while the Netherlands designed legislation only to limit the amount of use and the amount of drug distribution.